The Influence of Work-Life Balance on Employee Performance (Empirical Study at Telkomsel Regional Sumbagsel Office): (Empirical Study at Telkomsel Regional Sumbagsel Office) - Muhammad Brian Valery; Parama Santati; Muhammad Ichsan Hadjri (JPIM (Jurnal Penelitian Ilmu Manajemen), 2023)
This study aims to examine the influence of work-life balance on employee performance, an empirical study of the hybrid working system for Telkomsel Regional Sumbagsel office employees. The data that used on this study are primary data, with 64 employees as a sample, using a simple random sampling technique. The analytical method used is quantitative analysis with a simple regression analysis. The result of this study is work-life balance has a positive and significant influence on employee performance. It is recommended for the company to provide support from both superiors and colleagues to employees in order to achieve a balance of work and personal life while doing hybrid working.